"I am not a guinea pig": Parental opportunity hoarding and tracking reform in Germany. (March 2021) - Apple, Lana; Debs, Mira
PISA test data from 2000 to today have shown Germany's education system is one of the most inequitable within the OECD, with high correlations between student background and achievement outcomes. Scholars have identified the highly differentiated school structure, which tracks students as young as 10 years old, as a central cause. This scholarship has not evaluated why German tracking has proved difficult to reform over the last 20 years, despite evidence of negative outcomes. Using a case study of parents' actions in Hamburg, this paper employs a discourse analysis of debates surrounding a tracking reform to argue that opportunity hoarding—that is, parents with more social capital maintaining certain advantages through ingrained systems that are theoretically open to all—may contribute to why Germany's early tracking system persists despite evidence showing that it increases educational inequality. The findings presented have implications for an international discussion of tracking reform and opportunity hoarding.